Thermoelastic waves and velocity of their propagation in a dynamic related thermoelasticity - Шамровский, Александр Дмитриевич; Меркотан, Галина Викторовна (Eastern-European Journal of Enterprise Technologies, 2011)
In the presented work is investigated the influence of temperature on thermal and mechanic waves in half-space in a generalized constrained dynamic task of thermoelasticity